Recent Catalyst Technology Development in Residue Catalytic Cracking Unit: A Mini Review - Suhendra Suhendra; Zen Adi Laksana; Dhenok Widiastuti; Tita Griya Melyta (Universitas Ahmad Dahlan, 2019)
The use of fuel oil from year to year until now has experienced a rapid increase, due to increasing population growth in vehicle operations and the development of industries that require fuel. The position of renewable energy has not been able to shift the position of petroleum fuels to the needs of the world market. The RCC unit is secondary processing that converts heavy fraction hydrocarbons to light fraction hydrocarbons with the help of using catalysts into high-value petroleum products such as Naphtha, LPG, and Light Cycle Oil. RCC unit has three main parts of the process, namely riser, stripper, and regenerator, with the use of the main raw material of residue and using a catalyst. This paper aims at reviewing recent journals concerning the catalyst applied in the RCC unit. The basis of the RCC unit to be reviewed is from an existing RCC unit in Indonesia. The development of research on catalysts and regeneration technology in the RCC unit has experienced rapid development until now. It is expected that this paper can contribute to the future development and application of catalysts for the RCC unit, both for national and international levels.